Avaliação da qualidade da água da sub-bacia do Rio Piracicaba e da sua área de influência no reservatório da Usina Hidrelétrica de Sá Carvalho, Antônio Dias, MG, Brasil - Marluce Teixeira de Andrade Queiroz (2017)
The water resources play a fundamental role in the treatment of the principles and objectives of the National Environment Policy, National Water Resources Policy of the National Energy Plan and the degree of susceptibility in terms of quality and quantity, for the adequate planning and conservation that represent the foundation of prime importance in the context of river basins in Brazil. The objective of this study was to evaluate the influence of the reservoir of the Hydroelectric Power Plant (UHE- Sá Carvalho), located in Antonio Dias, Minas Gerais state, Brazil, in the surface waters of the Piracicaba sub-basin, MG, which is inserted in Doce River Hydrological Basin(BHRD).Surface water samples were collected from the reservoir of the UHE Sá Carvalho and in five points, located in different municipalities, along the Piracicaba River Hydrological Basin (BHRP) at P1: Fonseca; P2: Piracicaba river; P3: Nova Era; P4: Antônio Dias and P5: Ipatinga, in rainy, intermediaries and dry seasons. It was evaluates the parameters limnological, physical-chemical, bacteriological, series of metals (Al, As, Ca, Co, Cr, Fe, Mn, Na, K, Th, V e Zn) and Water Quality Index (WQI or IQA) were analyzed according to the CETESB (2006) and APHA (2005) and compared with the Maximum Allowable Concentration (MAC or MVP) established for lotic ecosystems Class 2 as the resolution of the National Environment Council (CONAMA) n.º 357 de 17/03/2005 (BRASIL, 2005). The deterioration of the aquatic body showed the relationship of high loads of pollution with the exploitation of natural resources and the existence along the BHRP of large companies to extract iron ore, metallurgical, extractive industries, agropastoral farms and absence of Sewage Treatment Stations (ETEs), with the exception of P5. The results reflected negatively in the quality of water. The waters quality in the area of influence of the UHE Sá Carvalho differed between localities covered in this study (BHRP) showing correlation with the use and occupation of the soil as a function of the nutrients load discharged. However not observed risk for aquatic life in the reservoir of the UHE Sá Carvalho